2015
DOI: 10.1051/0004-6361/201424212
|View full text |Cite
|
Sign up to set email alerts
|

Grand solar minima and maxima deduced from10Be and14C: magnetic dynamo configuration and polarity reversal

Abstract: Aims. This study aims to improve our understanding of the occurrence and origin of grand solar maxima and minima. Methods. We first investigate the statistics of peaks and dips simultaneously occurring in the solar modulation potentials reconstructed using the Greenland Ice Core Project (GRIP) 10 Be and IntCal13 14 C records for the overlapping time period spanning between ∼1650 AD to 6600 BC. Based on the distribution of these events, we propose a method to identify grand minima and maxima periods. By using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 55 publications
(64 reference statements)
4
76
2
Order By: Relevance
“…These numbers are similar to those estimated earlier by Usoskin et al (2007), although we note that more grand maxima are now identified. In contrast, these numbers are significantly lower than those recently estimated by Inceoglu et al (2015), who relied on a different type of analysis and set of criteria (somewhat less restrictive, leading to the identification of a larger set of events, which is essentially inclusive of the set of events we identified here, see Tables 1 and 2). Times of grand minima and maxima identified in this way are shown in Figs.…”
Section: New Constraints On the Temporal Distribution Of Grand Minimucontrasting
confidence: 74%
See 1 more Smart Citation
“…These numbers are similar to those estimated earlier by Usoskin et al (2007), although we note that more grand maxima are now identified. In contrast, these numbers are significantly lower than those recently estimated by Inceoglu et al (2015), who relied on a different type of analysis and set of criteria (somewhat less restrictive, leading to the identification of a larger set of events, which is essentially inclusive of the set of events we identified here, see Tables 1 and 2). Times of grand minima and maxima identified in this way are shown in Figs.…”
Section: New Constraints On the Temporal Distribution Of Grand Minimucontrasting
confidence: 74%
“…This makes terrestrial processes, in particular transport and deposition, a much more likely cause. Differences in the very long term Holocene trends between the two isotopes have previously been noted and ascribed to such terrestrial processes (Vonmoos et al 2006;Usoskin et al 2009;Steinhilber et al 2012;Inceoglu et al 2015). Climate change, in particular, is a likely cause because it affects the two isotopes in very different ways , with 14 C being sensitive to long-term changes in the ocean circulation (e.g., Hua et al 2015), while 10 Be is mainly sensitive to large-scale atmospheric dynamics.…”
Section: Fig 5 Corrected Sunspot Number Reconstructions Sn-14c-c (Pmentioning
confidence: 94%
“…This conclusion has been confirmed (e.g., Usoskin et al 2003c;Muscheler et al 2007) in the sense that quantitative solar-activity reconstructions, based on 10 Be and 14 C data series for the last millennium, yield very similar results, which differ only in small details. However, a longer comparison over the entire Holocene timescale suggests that, while centennial variations of solar activity reconstructed from the two isotopes are very close to each other, there might be a discrepancy in the very long-term trend (Vonmoos et al 2006;Inceoglu et al 2015;Usoskin et al 2016a), whose nature is not clear (climate changes, geomagnetic effects or model uncertainties).…”
Section: Comparison Between Isotopesmentioning
confidence: 97%
“…They compared the expected 10 Be variations computed from 14 C-based reconstruction of cosmic ray intensity with the actually measured 10 Be abundance at the sites and found that: (1) There is good agreement between the 14 C and 10 Be data sets, on different timescales and at different locations, confirming the existence of a common solar signal in both isotope data; (2) The 10 Be data are driven by the solar signal on timescales from about centennial to millennial time scales; (3) The synchronization is lost on short (<100 years) timescales, either due to local climate or chronological uncertainties (Delaygue and Bard 2011) but the solar signal becomes important even at short scales during periods of Grand minima of solar activity, (4) There is an indication of a possible systematic uncertainty in the early Holocene (cf. Vonmoos et al 2006;Inceoglu et al 2015;Usoskin et al 2016a), likely due to a not-perfectly-stable thermohaline circulation. Overall, both 14 C-and 10 Be-based records are consistent with each other over a wide range of timescales and time intervals.…”
Section: Comparison Between Isotopesmentioning
confidence: 99%
See 1 more Smart Citation